Aesthetic Dualities In Arabic Rhetoric Metaphor And Double Entendre As Examples/ الثنائيات الجمالية في البلاغة العربية الكناية والتورية أنموذجا - Abdel Ati, Ahmed Ali Mohamed; Issa, Koussoube; Saidoon, Musaed Amer Ebrahim; Hamidi, Tamer Ismail Mohamed Mohamed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The research aims to present an aesthetic perspective from the reality of Arabic rhetoric using the principle of aesthetic dualities, available in two rhetorical elements: metaphor (kinaya) and double entendre (tawriya). The study employed a descriptive-analytical method and focused on the extent to which the process of aesthetic dualities is available in the rhetorical device of metaphor and the rhetorical embellishment of double entendre. It also examines the potential aesthetics that highlight the impact of Arabic rhetoric in general and the value of these two devices. The research is divided into an introduction, a preface, and two main sections: Section One: Metaphor and Section Two: Double Entendre. The study resulted in a set of findings, the most prominent of which are: The research concluded that metaphor aims through the duality between direct and indirect expression to create novelty and intrigue in styles, distancing them from directness while achieving both expressions if necessary. In contrast, double entendre aims through semantic duality to reach one of the two meanings (the distant one) rather than the other (the near one), with the latter serving to reinforce the distant meaning (as understood in the concept of double entendre) at the expense of its counterpart, thereby achieving intrigue and stimulating the recipient’s mind, drawing their attention to the intended significance sought by the writer or the sophisticated language user.